Pharmacokinetics, Pharmacodynamics, and Safety of Edoxaban in Pediatric Subjects: A Phase I Single-Dose Study - Zou, Peng; Zahir, Hamim; Duggal, Anil; Pandya, Grishma; Jin, James; Leil, Tarek A (Clinical pharmacology and therapeutics, 2024)
This was an open-label, single-dose, phase I study to characterize the pharmacokinetics (PKs), pharmacodynamics (PDs), and safety of edoxaban in pediatric subjects from birth to 18 years at risk for venous thromboembolism (VTE). Children requiring anticoagulant therapy were enrolled into 5 age cohorts (0 to < 6 months (N = 12), 0.5 to < 2 years (N = 13), 2 to < 6 years (N = 13), 6 to < 12 years (N = 13), and 12 to < 18 years (N = 15)) receiving tablet or oral suspension of edoxaban at doses expected to be equivalent to 30 or 60 mg once daily (q.d.) in adult subjects with VTE. Sixty-six pediatric subjects were enrolled and completed the study. Edoxaban plasma concentration peaked between 1 and 3 hours and declined rapidly until 4-8 hours. The range of mean total apparent clearance across 5 age cohorts at low and high doses was 0.47 to 1.11 L/h/kg. The ranges of mean volume of central compartment and apparent peripheral volume were 2.31 to 3.59 L/kg and 1.92 to 4.14 L/kg, respectively. Across all age groups, the estimated median exposures were within the 0.5- to 1.5-fold of the median area under the plasma drug concentration-time curve (AUC) in adult subjects receiving corresponding doses (30 mg q.d. for low dose and 60 mg q.d. for high dose). In all age groups, PD parameters (prothrombin time, activated partial thromboplastin time, and anti-Factor Xa activity) showed a linear PK-PD relationship and were in line with previous adult data. The results support further evaluation of the pediatric doses in larger pivotal trials.